LENGTH-WEIGHT RELATIONSHIP IN FRESHWATER CAT FISH CLARIAS BATRACHUS (LINN.) - Shendge, A. N. (Journal of Indian Fisheries Association, 2009)
Clarias batrachus (Linn.), a common freshwater cat fish of Bhima river, has high economicvalue and considerable fishery importance. The length-weight relationship in the logarithmic wayfor this fish can be written as: Log W = 4.503717819 + 2.70681765 Log L This is close to the cubiclaw indicating the isometric growth of the fish in its natural habitat. The correlation coefficient (r)was found to be 0.9824 which showed a good relationship between the two parameters.Keywords: Clarias batrachus/ length-weight relationship, Bhima river.